A study on the functionality effects of potassium chloride in tocino - Madrio, Elpidio R. Jr.; Francisco, Ma. Leonora dL. (1999)
This study was conducted to determine the functionality effects of potassium chloride (KCl) concentration in tocino. From the three tocino recipes, the formulation standardized by the Bureau of Animal Industry was selected as the most acceptable formulation by 25 untrained panelist. The chosen formulation was then used to determine the acceptable levels of KCl incorporated in tocino at the following levels: 0%, 33.3%, 66.67% and 100%. The replacement level of up to 66.67% produced the acceptable rating. On the other hand, an acceptable rating was produced when the replacement level was increased to 100%. Physico-chemical tests were conducted to determine the functionality effects of KCl concentration incorporated at varying levels in tocino. It was observed that the cooking loss significantly increases as the replacement level increases. As for pH and WHC, no significant difference was observed in the values of four tocino samples. In purge analysis, the purge loss was low in tocino samples that use a mixture of sodium chloride and potassium chloride while high in tocino samples that use either of the two salts abovementioned.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat -- Preservation; Potassium chloride